Automatización del proceso de elaboración en la sección líquidos, utilizando el protocolo de comunicación Modbus en la empresa Jabonería Wilson S.A., durante el año 2015 - Chicango Cruz, Jennifer Mabel (2015)
This project involves the automation of the elaboration process of liquid detergents, using Modbus communication protocol, in the company Jabonería Wilson S.A.; which process of weighing of prime material, previously was held in empty tanks with the help of a scale, in which the exact amount in kilograms of the product ordered is entered, there were transported to the whisks and then were emptied into the elaboration tanks. This whole process took a long time, but now with the new installations of the company located in Calacalí, thanks for it's bigger space, allows to reduce the preparation time of the process, transport and manual weighing. The system consists of two parts: the first is a HMI that was developed by the company Amimechanical, which allows you to select which tank will be drawn up, downloading the product and the required amount thereof; the second part is programming a PLC Mitsubishi L series, for which a Modbus communication was configured and the counter measurements of a mass flow meter and two meters electromagnetic flow was obtained, these sensors allow controlling the opening-shut of the valves that control the ingress of products in the tanks and thus speed up the process. Due to the restriction of three sensors that supply products to five tanks, the process of the same material addition had to be restricted in the same tank as in different tanks, because the process operators are not going to know how much of the product is in the tanks.